Development of a speckle‐based portable device for in situ metrology of synchrotron X‐ray mirrors. (16th August 2016) - Kashyap, Yogesh; Wang, Hongchang; Sawhney, Kawal
Abstract : A portable device, using the speckle scanning technique, has been developed for in situ metrology of X‐ray mirrors at synchrotron light facilities. Abstract : A portable device for in situ metrology of synchrotron X‐ray mirrors based on the near‐field speckle scanning technique has been developed. Ultra‐high angular sensitivity is achieved by scanning a piece of abrasive paper or filter membrane in the X‐ray beam. In addition to the compact setup and ease of implementation, a user‐friendly graphical user interface has been developed to ensure that optimizing active X‐ray mirrors is simple and fast. The functionality and feasibility of this device have been demonstrated by characterizing and optimizing X‐ray mirrors.